DETEKSI FRAUDULENT FINANCIAL REPORTING MENGGUNAKAN ANALISIS FRAUD PENTAGON : STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG LISTED DI BEI TAHUN 2014-2016 - Erma Setiawati; Ratih Mar Baningrum (Universitas Muhammadiyah Surakarta, 2018)
This study aimed to analyze and obtain empirical evidence about the effect of pentagon fraud elements (pressure, opportunity, rationalization, competence, and arrogance) on detected fraudulent financial reporting. This research analyzes the influence of variable pressure proxied by financial stability, financial target, external pressure and personal financial needs, variable opportunity proxied by nature of industry, ineffective monitoring, and, quality of external auditor, variable rationalization proxied by change in auditor, variable arrogance proxied by frequent number of CEO’s pictures.Population of this study manufactured company in Indonesia Stock Exchange during year period 2014-2016 with a total sample 252 manufacture company by using purposive sampling method. Data analysis technique used was logistic regression analysis processed by using program SPSS 23 for Windows. The results of this study show that only the variable financial target have an effect to detected fraudulent financial reporting. This study hasn’t shown that financial stability, external pressure , personal financial needs, nature of industry, ineffective monitoring, quality of external auditor, change in auditor, change of directors, frequent number of CEO’s pictures have an effect to detected fraudulent financial reporting.Keywords: Fraud Pentagon, Fraud Diamond, Fraud Triangle, Fraudulent Financial Reporting, Manufactured Sector Fraud.